New and little known Brachodidae from tropical Asia and Papua New Guinea (Lepidopera, Cossoidea) - Kallies, Axel (Zootaxa, 2013)
In this study nine new species and a new genus of Brachodidae are described from tropical Asia and Papua New Guinea. Synechodes polias sp. nov. and Synechodes tamila sp. nov. are described from Sulawesi and southern India, respectively. A new genus, Saccocera gen. nov. (type species Miscera orpheus Kallies, 2004), is described to accommodate five species occurring from Taiwan and Sumatra across Melanesia to Papua New Guinea. It differs significantly from the related genera Miscera Walker, 1863 and Synechodes Turner, 1913 in morphological details of the head and the male and female genitalia. Two species of Saccocera are described here, Saccocera panaras sp. nov. from Papua New Guinea and Saccocera miangkabau sp. nov. from Sumatra. Furthermore, Miscera minahasa sp. nov. and Paranigilgia mariannae sp. nov. are described from Sulawesi, Paranigilgia brandti sp. nov. and Nigilgia atribractea sp. nov. from Papua, and Nigilgia browni sp. nov. is described from Christmas Island. Finally, Synechodes heppneri Kallies, 1998 syn. nov. is reverted to a junior synonym of Synechodes coniophora Turner, 1913. Nigilgia anactis Diakonoff, 1982 is figured for the first time and its distribution in Asia is discussed.